PECULIARITIES OF IRISH EMIGRATION AND DEVELOPMENT OF THE DIASPORA IN THE GREAT BRITAIN - Marusynets, Marianna (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2024)
The article examines the peculiarities of Irish emigration and the development of the Irish diaspora in Great Britain, which includes ethnic Irish people and their descendants outside Ireland. The Irish diaspora is the largest minority group in England and Scotland and constitutes the largest immigrant community in Great Britain. It is noted that the historical relations between Great Britain and Ireland differ from those with other EU countries. Irish citizens enjoy more favorable conditions in Great Britain than citizens of other EU countries. The author emphasizes the importance of the Anglo-Irish Treaty of 1921 for the introduction of a legal framework for the protection of the rights of citizens of both countries and the Common Travel Area Agreement (CTA) for the preservation of the special legal status of Irish citizens in the UK. The CTA guarantees the mutual rights of Irish and UK citizens in each other’s territories. It is proved that the Irish diaspora has played an important role in the socio-economic and political development of Great Britain, in particular in construction and transport, especially in England and Scotland. The Irish have created emigrant networks, including the daily newspaper The Irish Post and the Federation of Irish Societies. There is a strong political presence of the Irish diaspora in Great Britain. An assessment is given of the conflict in Northern Ireland, which has caused a wide resonance among the Irish diaspora in Great Britain. Some diaspora organisations condemned the campaign of the Irish Republican Army (IRA). Militant diaspora activists supported republican aspirations and criticised British “imperialism”.